Impact of the Russian-Ukrainian War on the Prices of Commodities Exported by CEMAC Countries (Global Journal of Human-Social Science, 2023)
This article assesses the impact of the Russian- Ukrainian war on the prices of commodities exported by CEMAC countries This work takes place in a context where CEMAC countries whose export revenues come mainly from raw materials and energy are seeing an increase in the prices of the latter As a result knowledge of the real impact of this war on the prices of these products is important for the development of relevant policies that can enable these countries to benefit Using a DSGE model simulations were conducted on the prices of these commodities without war and with war The results suggest that the impact is more pronounced on the prices of gas oil and palm oil so that it takes at least 40 months to be restored
Keywords: russian-ukrainian war; commodities; DSGE model